Oligomeric assembly of the gatekeeper InvE orchestrates hierarchical type III protein secretion in Salmonella Typhimurium - Tingting Wang; Liyan Zhu; Emily Guo; Chunxiang Wu; Florian Schueder; María Lara-Tejero; Jorge E. Galán (Proceedings of the National Academy of Sciences, 2026)
Type III secretion systems (T3SS) are critical virulence machines in many Gram-negative bacteria, enabling hierarchical secretion of translocases followed by effectors. In the Salmonella enterica serovar Typhimurium SPI-1 T3SS, the regulatory protein InvE (SctW) enforces this order. Here, we show that InvE assembles into tetramers and higher-order oligomers and that oligomerization is essential for function. A 2.4 Å cryo-electron microscopy (cryo-EM) structure reveals a tetramer built as a dimer of antiparallel dimers. Photocrosslinking maps one set of residues to the interdimer seams in this tetramer, while crosslinks from additional sites suggest lateral docking between dimers in alternative registries in vivo. Blue-native electrophoresis and SEC–MALS detect native high-molecular-weight species consistent with such assemblies. DNA-PAINT superresolution microscopy confirms the presence of higher-order InvE oligomers in vivo. Charge-reversal mutations that disrupt oligomerization collapse InvE to monomers and abolish secretion, effector translocation, invasion, and virulence. Together, these data define an oligomerization-based switch in which InvE reuses the dimeric face to form higher-order contacts that govern the transition from translocase to effector secretion.